METODE GURU DALAM MENINGKATKAN MOTIVASIPESERTA DIDIK KELAS III UNTUK MENGHAFAL AL-QUR’AN DIRUMAH AL-QUR’AN AKHLAK MULIA DUSUN SADAYAN DESA SABAYAN KECAMATAN SAMBASTAHUN 2022 - Noviyanti Noviyanti; Eliyah, Mauizatul Hasanah (ADISAM PUBLISHER, 2026)
The purpose of this reseach is to find out: 1) How the teachers plan to increase the motivation of third grade students to memorize the Qur’an at Rumah Qur’an Akhlak Mulia , Sadayan Hamlet, Sebayan Hamlet, Sambas District, in 2022; 2) How do teachers improve the motivation of third grade students to memorize the Qur’an at Rumah Qur’an Akhlak Mulia,Sadayan hamlet,Sebayan Village, Sambas District, Year 2022; and 3) What Are the implications of teachers in increasing the motivation of third grade students to memorize the Qur’an at Rumah Qur’an Akhlak Mulia, Sadayan Village, Sebayan Village, Sambas District, Year 2022. The reseach uses a qualitative approach with a phenomenological type of reseach. The data collection techniques used were interviews, observation and documentation. The data analysis techniques used are data reduction, data presentation, verification and drawing conclutions. The results of the research show that 1) the teacher’s planning to increase the motivation of class III students to memorize the Al-Qur’an at the Rumah Qur’an Akhlak Mulia, sadayan hamlet, sabayan village, Sambas District in 2022, the teacher prepares material to motivate and maintain the enthusiasm of the students in memorize the qur’an. Target that has been set, and complete juz 30 and finally cary out an evaluation; 2) theacers implication increasing class students motivation for class III students at Rumah Qur’an Akhlak Mulia; 3) The teachers implementation in increasing the motivation of class III students to memorize the A-Qur’an at Rumah Qur’an Akhlak Mulia,Sadayan Hamlet, Sabayan Vilallage, Sambas District in 2022, start from the initial activities, arranging class condition, taking attendance of students and muroja’ah. Next, the core part is preparing media, material III for memorizing the qur’an at the Rumah Qur’an Akhlak Mulia, Sadayan Hamlet, Sabayan Village, Sambas District in 2022, the existence of motivation and methods. This has an impact on the students memorization targets that have been achieved. Although there are some students who have not been able to achievethis